Miss O'Keefe - Patten, Christine T. (UNM Press Albuquerque, NM, 1992)
In 1983, Christine Taylor Patten was hired as one of the people who took care of Georgia O$1 (BKeeffe, then ninety-six. Also an artist, Patten served as nurse, cook, companion, and friend to the older woman. This intimate account of the year of Patten$1 (Bs employment offers a rare glimpse of O$1 (BKeeffe$1 (Bs daily life when she could no longer see well enough to paint.s
63453
Keywords: Georgia O'Keefe -- Artists; Old age -- Care givers; Women -- Friendship